(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Taxation is widely seen as a hallmark of a civilized society. Taxation underwent distinct evolution and development within the context of the prominent ancient empires. The notions that underwent development were disseminated to other empires and cultures, hence facilitating the establishment and adoption of tax principles.